Optimalisasi kinerja tim proyek dengan memanfaatkan metode CPM dan PERT dalam pekerjaan pematangan lahan - Efrizon, Efrizon; Masydzulhak Djamil Mz; Sugeng Santoso; Ahmad H. Sutawijaya (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to conduct a study on optimizing work performance on the work team forland development projects at PT PANARUB INDUSTRY in Brebes, Central Java, usingthe CPM and PERT methods. Significant delays in project completion become the basisfor testing all project activities starting from planning through work breakdownstructures, determining duration, interrelationships between activities and conductingstandard deviation tests using a normal distribution table to determine the probability ofproject completion by crashing which is the responsibility of full responsibility of theproject implementation team led by the Project Manager. The results of the threescheduling studies, namely scheduling according to the initial time of the project durationplanning according to the CPM and PERT methods can cut work time significantly so thatit has an impact on the work performance of the project team. The CPM and PERTmethods really help the project team's performance, especially in accelerating theoptimization of time and cost efficiency, and the actions taken are based on accuratecalculations.